César Vallejo and the staging of ideologies: Towards a new aesthetics of reality - Merino, Antonio (2022)
César Vallejo’s universe, which includes biography, works, literary criticism, studies, editions, and publications, is complex and contradictory. When we speak, for example, of his first readings or incursions into Vallejo’s works, as in the case of El romanticismo en la poesía castellana (1915), we are defining a working methodology that runs through the old positivist discourse of Comte, S. Mill or H. Taine, reinforced by the readings of Schlegel, Le Bonn, Menéndez Pidal, Dante, Petrarca, Byron and Schiller, which cemented his knowledge of literary reality and which, over the years, would open the doors to a new «avant-gardism» which proved to be not exempt from some infelicities of form.